IMPLEMENTASI PAJAK PERTAMBAHAN NILAI (PPN) PADA HASIL PERTANIAN DALAM PERSPEKTIF ISLAM - Romi Adetio Setiawan (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2015)
Implementation of Value Added Tax on agricultural product in Islamic Perpective. Toreduce Indonesia's dependence on foreign debt, the government tightened fiscal policy, by increasingthe tax revenue in the Budget Revenue and Expenditure or APBN-P 2013 that reached Rp 916.2trillion or 92.06 percent of the target of Rp 995.2 trillion. Of course, to increase tax revenues, thegovernment has made tax reform one of them by applying the Value Added Tax (VAT) for all types ofgoods including agricultural products. Indonesia is an agrarian country, and farmers are the livelihoodof the majority, so it is necessary for the government to consider tax for agricultural products, and toensure the people are not suffering by implementation of agri-products taxes. VAT collection is not atissue in Islam, although there are some Wahhabi clerics that forbid it, but jumhur scholars agree thatVAT is allowed by adapting the principle of maslahah and justice, thus, the taxes collected will beadapted to the religious and juridical norms